An indirect generation of 1D MII-2, 5-dihydroxybenzoquinone coordination polymers, their structural rearrangements and generation of materials with a high affinity for H2, CO2 and CH4. Issue 4 (6th January 2016) - Abrahams, Brendan F.; Dharma, A. David; Dyett, Brendan; Hudson, Timothy A.; Maynard-Casely, Helen; Kingsbury, Christopher J.; McCormick, Laura J.; Robson, Richard; Sutton, Ashley L.; White, Keith F.
Abstract : 1D coordination polymers undergo transformations upon desolvation to yield sorbent materials. Abstract : A series of solid-state structural transformations are found to accompany desolvation of relatively simple coordination polymers to yield materials that exhibit unexpected gas sorbing properties. Reaction of 1, 2, 4, 5-tetrahydroxybenzene with M II salts (M = Mg, or Zn) in an alcohol/water solution in the presence of air affords cis -M II (C6 H2 O4 −II )(H2 O)2 ·2H2 O· x ROH, (M = Mg, or Zn), crankshaft-like chains in which the absolute configurations of the chiral metal centres follow the pattern ⋯Δ Δ Λ Λ Δ Δ Λ Λ⋯, and are hydrogen bonded together to generate spacious channels. When crystals of the crankshaft chain are air dried the crystals undergo a single crystal-to-powder rearrangement to form linear trans -M II (C6 H2 O4 −II )(H2 O)2 chains. Further dehydration yields microporous solids that reversibly sorb H2, CH4 and CO2 with high sorption enthalpies.